Associated Factors of Hepatitis B Infection among Pregnant Women attending Antenatal Clinic in Kitagata Hospital, Sheema District. A Cross-sectional Study. - Areebahona, Edgar (Student’s Journal of Health Research Africa, 2022)
Background: The study assessed the associated factors of hepatitis B infection among pregnant women attending antenatal clinic in Kitagata hospital, Sheema district, and specifically sought to find out the prevalence, the knowledge, and the risk factors of hepatitis B infection among pregnant women attending antenatal clinic in Kitagata hospital, Sheema district. Methodology: The study used a cross-sectional study design while employing a quantitative data collection approach where a pretested questionnaire designed based on the specific objectives was used to collect data from 100 respondents following the informed consent of the participant. Results: The prevalence of Hepatitis B among Pregnant Women attending Antenatal Clinic in Kitagata Hospital, Sheema District is 4.0%. The majority (51%) of the respondents were between 20-25 years, (53%) were cohabiting, (42%) had attained secondary education, (50%) were Catholic, (52%) were unemployed, (90%) had a gestation period of 7-9 months,(40%) were Banyankole and (4.0%) were positive of hepatitis B virus. Majority (63%) had ever heard about Hepatitis B infection (57.1%) heard about it from a health worker, (55%) knew Hepatitis B could be found in the blood, (60%) understood Hepatitis B, (55%) knew the transmission routes of Hepatitis B, (80%) knew that Hepatitis B vaccine exists, (93%) had not been vaccinated and (75%) did not know the symptoms. Conclusion: The prevalence of hepatitis B infection among pregnant women was high whereas the knowledge regarding hepatitis B infection was moderate and the predisposing factors to hepatitis B infection were majorly having two sexual partners and having a tooth extraction. Recommendation: I recommend the provision of mandatory free screening and vaccination services by the government to the pregnant mothers since it will help in discovering the number of cases hence scaling up the type of care and treatment needed.